2018
DOI: 10.1002/2211-5463.12496
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐17 as a promising diagnostic biomarker of gastric cancer: An investigation combining TCGA, GEO, meta‐analysis, and bioinformatics

Abstract: Integrated studies of accumulated data can be performed to obtain more reliable information and more feasible measures for investigating potential diagnostic biomarkers of gastric cancer ( GC ) and to explore related molecular mechanisms. This study aimed to identify micro RNA s involved in GC by integrating data from The Cancer Genome Atlas ( TCGA ) and Gene Expression Omnibus. Through our analysis, we identified hsa‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Currently, multiple miRNAs have been investigated as candidate GC biomarker. Studies found that miR-17-5p was upregulated in tissue samples of GC patients, while no consensus has been made about its expression in the peripheral blood 2830. We found that the upregulated miR-17-5p in plasma was superior to other miRNAs in GC detection.…”
Section: Discussionmentioning
confidence: 52%
“…Currently, multiple miRNAs have been investigated as candidate GC biomarker. Studies found that miR-17-5p was upregulated in tissue samples of GC patients, while no consensus has been made about its expression in the peripheral blood 2830. We found that the upregulated miR-17-5p in plasma was superior to other miRNAs in GC detection.…”
Section: Discussionmentioning
confidence: 52%
“…Besides, we also found a close co-expression relationship between 3 miRNAs and genes, including hsa-miR-17, hsa-miR-23c, and hsa-miR-326. Among them, hsa-miR-17 was considered as a promising diagnostic biomarker of gastric cancer [37] and colorectal cancer [38], and hsa-miR-23c was involved in the pathogenesis of non-small cell lung cancer [39]. Furthermore, only hsa-miR-326 and its co-expressed gene ELFN2 was significantly associated with the survival time of EC patients.…”
Section: Discussionmentioning
confidence: 99%
“…A cut-off value of 7.075 is applied for miR-421 to detect GC [75]. Similarly, several oncogenic proliferation-triggering miRNA such as miR-543 [76] targeting Sirtuin 1 (SIRT1), miR-106a targeting tissue inhibitor of metalloproteinases 2 (TIMP2) [77], or miR-17 which targets a number of genes involving in tumorigenesis, disease progression, invasion, and metastasis of GC [78,79] have been suggested as candidate markers for GC diagnosis.…”
Section: Diagnostic Potential Of Ctc In Gcmentioning
confidence: 99%